2001
DOI: 10.2514/2.1382
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Hypersonic Boundary Layers by Porous Coatings

Abstract: A second-mode stability analysis has been performed for a hypersonic boundary layer on a wall covered by a porous coating with equally spaced cylindrical blind microholes. Massive reduction of the second mode amplication is found to be due to the disturbance energy absorption by the porous layer. This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(58 citation statements)
references
References 20 publications
4
53
1
Order By: Relevance
“…Previous numerical simulations [3] have suggested that UAC performance increases with porosity, and our parametric study tends to confirm this result. Overall, the amplitude of the reflection coefficient decreases with higher porosity, as the scattering and absorption of acoustic waves by the UAC is enhanced.…”
Section: E Guidelines For Uac Designsupporting
confidence: 74%
See 2 more Smart Citations
“…Previous numerical simulations [3] have suggested that UAC performance increases with porosity, and our parametric study tends to confirm this result. Overall, the amplitude of the reflection coefficient decreases with higher porosity, as the scattering and absorption of acoustic waves by the UAC is enhanced.…”
Section: E Guidelines For Uac Designsupporting
confidence: 74%
“…The width 0:1 was found to be adequate to accurately resolve frequencies up to f f H=a 0 2. For typical UAC parameters, this range of frequencies corresponds to the ultrasonicfrequency band and is sufficient to capture the frequency of the most amplified second-mode instability waves observed in experiments [4,13] and numerical simulations [3,14,15].…”
Section: B Computational Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous experiments and numerical simulations, papers [1,3,4,5] demonstrated that porous materials on the flat plate and cone surface in a hypersonic flow suppress disturbances arising in the boundary layer, extend the laminar flow regime, and reduce the friction drag. These phenomena are based on dissipation of the energy of acoustic disturbances, which are a dominating mode of instability of a hypersonic boundary layer, owing to friction in pores of the coating.…”
Section: Figure 1 Permeable Highly Porous Cellular Materials (Hpcm): mentioning
confidence: 99%
“…The cause of the transition in hypersonic gradientless boundary layers is high frequencies unstable disturbances so called second mode disturbances [1]. On the passive porous coating with microstructure second mode disturbances grows slower than on the smooth surface [2]. The ability to delay transition by passive porous coatings are shown in several works [2 -4].…”
Section: Introductionmentioning
confidence: 99%